2018
DOI: 10.1007/s40145-018-0281-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of h-BN/Yb4Si2O7N2 composites

Abstract: A series of h-BN based composites with Yb 4 Si 2 O 7 N 2 as a secondary phase were successfully synthesized by an in situ reaction hot pressing method. It was found that the relative density and room-temperature mechanical properties monotonically increased with increasing the content of Yb 4 Si 2 O 7 N 2 from 20 to 50 vol%. When 50 vol% Yb 4 Si 2 O 7 N 2 was introduced, the relative density of the composite reached 98.75%, and its flexural strength, compressive strength, fracture toughness, and hardness reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…2. A similar peak slightly shied by partial substitution of Ba 2+ for [Bi 0.5 (Na 0.80 K 0.20 )] 2+ and Zr 4+ for Ti 4+ was reported by Chen et al 30 in the BNKT-BZT system. They also found that the (110) peak shied to lower 2q angles could produce an increase in the lattice constant and the unit cell dimension with increasing BZT fraction.…”
Section: Resultssupporting
confidence: 85%
“…2. A similar peak slightly shied by partial substitution of Ba 2+ for [Bi 0.5 (Na 0.80 K 0.20 )] 2+ and Zr 4+ for Ti 4+ was reported by Chen et al 30 in the BNKT-BZT system. They also found that the (110) peak shied to lower 2q angles could produce an increase in the lattice constant and the unit cell dimension with increasing BZT fraction.…”
Section: Resultssupporting
confidence: 85%
“…Many work has been done on the relationship between strength and structure [16][17][18][19][20][21][22][23][24]. Some empirical formulas and fracture models have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The strong sp2 covalent bonds combining B and N atoms result in a very low atomic diffusion rate even at high sintering temperatures, which makes h-BN ceramics hard to be densified during sintering [15,16] [17][18][19][20][21][22][23], has been widely proven to be an effective method to improve the sinterability of h-BN ceramics as these oxides can form liquid phases at high sintering temperatures and fill these pores between plate-like h-BN grains with the "house of cards" structure.…”
Section: Introductionmentioning
confidence: 99%